2006
DOI: 10.1093/jnci/djj189
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Erythropoietins and Cancer Patients: Updated Meta-Analysis of 57 Studies Including 9353 Patients

Abstract: This is an updated systematic review of 57 trials and 9353 cancer patients from articles, abstracts, and reports published between January 1, 1985, and April 30, 2005, on the effects of epoetin alfa and beta (i.e., epoetin) and darbepoetin alfa (i.e., darbepoetin). We included randomized controlled trials comparing epoetin or darbepoetin plus red blood cell transfusion with red blood cell transfusion alone for prophylaxis or treatment of anemia in cancer patients with or without concurrent antineoplastic thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
336
6
19

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(374 citation statements)
references
References 53 publications
13
336
6
19
Order By: Relevance
“…Within this, the relative risk of a thrombo-embolic event was increased by 67% in the treated group compared with the control group ( RR =1.67, 95% CI =1.35 to 2.06). [5] However, similar to the aforementioned articles, there were no findings of mesenteric thrombosis as a thrombotic complication of erythropoiesis-stimulating drugs. [313]…”
Section: Discussionmentioning
confidence: 63%
“…Within this, the relative risk of a thrombo-embolic event was increased by 67% in the treated group compared with the control group ( RR =1.67, 95% CI =1.35 to 2.06). [5] However, similar to the aforementioned articles, there were no findings of mesenteric thrombosis as a thrombotic complication of erythropoiesis-stimulating drugs. [313]…”
Section: Discussionmentioning
confidence: 63%
“…While certain studies observed beneficial effects (16)(17)(18), a lower survival rate was found in head-and-neck and breast cancer (22,23). apart from unclear effects on the tumor growth itself, systemic side effects including deep venous thrombosis or arterial hypertension may have worsened the patient outcome (24).…”
Section: Discussionmentioning
confidence: 99%
“…Eine Eisenersatztherapie ist die wichtigste therapeutische Maßnahme bei der krebsassoziierten Anämie; aufgrund der hepcidinbedingten Eisenverwertungsstörung ist allerdings das Ansprechen oft eingeschränkt, sodass eine begleitende Erythropoetintherapie, insbesondere bei der Chemotherapie-assoziierten Anämie, häufig notwendig wird [89,90]. Ein erhöhtes Thromboserisiko (RR 1,67) unter Erythropoese-stimulierenden Agenten stellt auch bei Malignompatienten ein erhebliches Problem dar [91]. Wie bei der renalen Anämie verursacht Erythropoetin einen funktionellen Eisenmangel, sodass eine begleitende Eisentherapie benötigt wird, um ein optimales Ansprechen zu erzielen [92,93].…”
Section: Eisenmangel Thrombozytose Und Erythropoetin Bei Chronischerunclassified